Maternal and Neonatal Outcomes of Dengue Fever in Pregnancy: A Cross-Sectional Study - Ferdous, Bilkis; Rahman, Md Mostafizur; Halim, Tanzila; Khatun, Hasina; Mohammad, Abu (Medicine Today, 2025)
Introduction: Dengue fever is a significant public health concern, particularly in tropical and subtropical regions, and poses risks to pregnant women and their infants. This study aims to evaluate dengue fever's maternal and neonatal outcomes during pregnancy. Materials and Methods: A cross-sectional study was conducted over one year, from January 2023 to June 2024, at Bangabandhu Sheikh Mujib Medical University (BSMMU) and Ibn Sina Diagnostic & Consultation Center, Malibagh total of 200 pregnant women diagnosed with dengue fever were included in the study. The sample size calculation was based on an expected prevalence of adverse maternal outcomes of 20% in dengue-infected pregnancies, with a confidence level of 95% and a margin of error of 5%. Data regarding maternal demographics, clinical characteristics, and neonatal outcomes were collected and analyzed. Results: Among the 200 pregnant women, the mean age was 27.3 ± 6.1 years, with a majority (65%) in their third trimester. Thrombocytopenia was observed in 120 (60%) women, with severe cases (platelet count <50,000/μL) in 30 (15%). Maternal complications included postpartum hemorrhage in 25 (12.5%), acute kidney injury in 15 (7.5%), and acute respiratory distress syndrome in 10 (5%). The overall maternal mortality rate was 5% (10 women). Neonatal outcomes revealed 10 (5%) stillbirths, 5 (2.5%) neonatal deaths, and 22 (12%) low birth weight infants and 18(8%) prematurity. Conclusions: Dengue infection during pregnancy is associated with maternal and neonatal morbidity and mortality. Enhanced awareness, early diagnosis, and management strategies are crucial to mitigate the risks of dengue in pregnant women. Medicine Today 2025, Vol.37 (1): 5-8